VISEGRAD GROUP: A DIFFERENT VIEW ON THE EUROPEAN POLICY - A. Y. Kolianov (Дискурс)
The article contains author’s thoughts about history and development of the Visegrad Group as an alliance of four Central European states: Czech Republic, Slovakia, Poland and Hungary. The author analyzes its role and place in the modern European policy.